Assembling humanitarianism in the Cold War: The role of the Red Cross in the Bay of Pigs prisoner exchange. (October 2022) - Schech, Susanne
Abstract: This paper examines humanitarian relations between Cuba and the US at the height of Cold War conflict. After the attempted invasion of Cuba at the Bay of Pigs in 1961 to overthrow the Cuban government had resulted in a memorable defeat for the United States of America, an unusual humanitarian operation in 1962-63 secured the release of the prisoners of war in exchange for food and medical supplies. Framing the Prisoner Exchange Project (PEP) as an assemblage helps to understand how humanitarian interventions can succeed in situations where diplomatic relations are severed, and without involving international organisations as mediators. I analyse how the project brought diverse non-state actors together under the banner of humanitarianism, as well as non-human elements including supplies, ships, aircrafts, documents, and affective elements such as desire and hospitality. The national Red Cross Societies of America and Cuba managed to successfully carry out the exchange through constant relational work and mechanisms to render the project technical. This case study offers important lessons about the entanglement of humanitarian and development work, and how the involvement of Red Cross Societies unsettled hierarchies between donors and recipients and traditional geographies of humanitarianism. Highlights: Focuses on the exchange of Bay of Pigs prisoners for medicines and food in 1962. Explores the emergence of humanitarian action through an assemblage theory lens. Analyses the civil society role through the American Red Cross archive. Highlights the relational work between American and Cuban Red Cross societies.